2020
DOI: 10.1111/een.12914
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of two termite‐eating specialists (Araneae)

Abstract: 1. Competition among closely-related specialist predators has rarely been studied, and thus the mechanism of their coexistence remains enigmatic. Interspecific competition among specialised co-occurring predators capturing termites should be high. 2. Here we investigated various niche dimensions, namely temporal, spatial and trophic, of a couple of jumping spider species of the genus Stenaelurillus (Stenaelurillus guttiger and S. modestus) from South Africa, to find whether these two species co-exist and along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…In interspecific competition terms, spiders rarely compete for food, especially in web‐spinners (Wise, 1993), but this can sometimes be significant between congeneric species or species belonging to the same family (Michalko et al, 2016; Michalko & Pekár, 2015; Nieto‐Castañeda & Jiménez‐Jiménez, 2009; Nyffeler et al, 1986). Some studies have shown that arachnids avoid competing by adopting strategies, such as spatial partitioning (Cumming & Wesołowska, 2004; Harwood et al, 2003; Michalko et al, 2016; Pekár et al, 2020; Villanueva‐Bonilla et al, 2019), temporal partitioning (are active or breed on different days or times of the year, respectively; Herberstein, 1997; Herberstein & Elgar, 1994; Ward & Lubin, 1992) or trophic partitioning (consume prey of different types or sizes according to their own trophic guild, size and food preferences; Nieto‐Castañeda & Jiménez‐Jiménez, 2009; Richardson & Hanks, 2009; Tahir et al, 2012). However, the contribution of interspecific competition to the structuring of tree hollow spider communities and their mechanisms is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In interspecific competition terms, spiders rarely compete for food, especially in web‐spinners (Wise, 1993), but this can sometimes be significant between congeneric species or species belonging to the same family (Michalko et al, 2016; Michalko & Pekár, 2015; Nieto‐Castañeda & Jiménez‐Jiménez, 2009; Nyffeler et al, 1986). Some studies have shown that arachnids avoid competing by adopting strategies, such as spatial partitioning (Cumming & Wesołowska, 2004; Harwood et al, 2003; Michalko et al, 2016; Pekár et al, 2020; Villanueva‐Bonilla et al, 2019), temporal partitioning (are active or breed on different days or times of the year, respectively; Herberstein, 1997; Herberstein & Elgar, 1994; Ward & Lubin, 1992) or trophic partitioning (consume prey of different types or sizes according to their own trophic guild, size and food preferences; Nieto‐Castañeda & Jiménez‐Jiménez, 2009; Richardson & Hanks, 2009; Tahir et al, 2012). However, the contribution of interspecific competition to the structuring of tree hollow spider communities and their mechanisms is unknown.…”
Section: Introductionmentioning
confidence: 99%